2021
DOI: 10.5194/angeo-39-357-2021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the residual mean meridional circulation at different stages of sudden stratospheric warming events

Abstract: Abstract. Ensemble simulation of the atmospheric general circulation at altitudes up to the lower thermosphere is performed using the 3-D nonlinear mechanistic numerical model MUAM. The residual mean meridional circulation (RMC), which is the superposition of the mean Eulerian and wave-induced eddy components, is calculated for the boreal winter. Changes in the vertical and meridional RMC velocity components are analysed at different stages of a simulated composite sudden stratospheric warming (SSW) event aver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 56 publications
0
21
0
Order By: Relevance
“…Nowadays, there is a program that combines interactive models to compare their ability to reproduce the QBO (Butchart et al., 2018). As it was stated above, the MUAM is not able to reproduce self‐consistently stratospheric QBO (unlike major SSW events; Koval et al., 2021), hence the simulations require specifying background and initial hydrodynamic fields for years with different QBO phases.…”
Section: Determination Of the Qbo Phasesmentioning
confidence: 99%
See 3 more Smart Citations
“…Nowadays, there is a program that combines interactive models to compare their ability to reproduce the QBO (Butchart et al., 2018). As it was stated above, the MUAM is not able to reproduce self‐consistently stratospheric QBO (unlike major SSW events; Koval et al., 2021), hence the simulations require specifying background and initial hydrodynamic fields for years with different QBO phases.…”
Section: Determination Of the Qbo Phasesmentioning
confidence: 99%
“…For better visibility, the vertical component is multiplied by 200. The meridional and vertical components of the residual mean meridional circulation in terms of the transformed Eulerian mean (TEM) are obtained from the ensembles of hydrodynamic fields simulated with the MUAM using standard formulas (e.g., Koval et al., 2021): truev¯0.17em=truev¯1trueθ¯/z()vθtrue¯H+truevθ¯zvθtrue¯θ¯z2trueθ¯z2, $\bar{v}\,\ast =\bar{v}-\frac{1}{\partial \bar{\theta }/\partial z}\left(-\frac{\bar{{v}^{\prime }{\theta }^{\prime }}}{H}+\frac{\partial \bar{{v}^{\prime }{\theta }^{\prime }}}{\partial z}-\frac{\bar{{v}^{\prime }{\theta }^{\prime }}}{\sfrac{\partial \bar{\theta }}{\partial z}}\frac{{\partial }^{2}\bar{\theta }}{\partial {z}^{2}}\right),$ truew¯0.17em=truew¯+1a0.17emcos0.17emφ1θ¯z()sin0.17emφtruevθ¯+cos0.17emφ()truevθ¯φvθtrue¯trueθ¯/z2trueθ¯zφ, $\bar{w}\,\ast =\bar{w}+\frac{1}{a\,cos\,\varphi }\frac{1}{\sfrac{\partial \bar{\theta }}{\partial z}}\left(-sin\,\varphi \bar{{v}^{\prime }{\theta }^{\prime }}+cos\,\varphi \left(\frac{\partial \bar{{v}^{\prime }{\theta }^{\prime }}}{\partial \varphi }-\frac{\bar{{v}^{\prime }{\theta }^{\prime }}}{\partial \bar{\theta }/\partial z}\frac{{\partial }^{2}\bar{\theta }}{\partial z\partial \...…”
Section: Zonal‐mean Circulation Up To Thermospheric Heightsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MUAM includes a parameterization of thermal and dynamical effects produced by mountain waves 32 and a spectrum of non-orographic gravity waves 33 . Numerous analyses have been carried out to validate MUAM, which have shown that it correctly reproduces the structure of the atmospheric circulation, PWs, and tides (e.g., 8,9,21,34,35 ), sudden stratospheric warmings 36 , as well as the resonance properties of the atmosphere (normal atmospheric modes) 20 .…”
Section: Methods and Approachesmentioning
confidence: 99%